Deutsche Städte im Luftkrieg - eine Schadensbilanz auf der Basis der Wohnungstotalzerstörungen - Hohn, Uta (ERDKUNDE, 1990)
This paper is the first one to present a quantitative account of war damage sustained by German towns for the area of the two post-war German states, taking the proportion of totally destroyed homes as a basis for scientific investigation. In every town, evidence of the degree of total destruction of homes is based on evaluation and adaptation of extensive and often contradictory statistical data. In this, enquiries made with town administrations and archives of the Federal Republic and the then GDR in 1984 and 1987 served to complement the material or to allow checking of the figures in question. The research report provides a survey of the course taken by the war in the air, shows the problems occurring in connection with the inventory of damage, and uses the results as a basis for describing the regional differences in the destruction of homes in German towns and cities. Degrees of total destruction of homes established for large- and medium-sized towns are shown in fig. 2. This, however, includes those medium-sized towns which registered a total loss of homes of at least one fifth of the building-stock. There is evidence that the towns of the former GDR suffered overall smaller losses than those of the Federal Republic. The map of the main damage region clearly shows up, moreover, the Rhine-Ruhr, Rhine-Main, and Rhine Neckar areas, the ravaged zones along the western border, in the south of the Saarland, in the southern Rhineland Palatinate, as well as along the Oder river and the hard-hit German port-towns. Fig. 3 represents the small towns (1939: 5,000-20,000 inhabitants), which were affected by major destruction of homes. In areas which saw air-raids and artillery shelling during the advance of the Allied forces in1944-45 they, too, form ravaged regions. This applies to the western Münsterland, the lower Rhine region, the Eifel, the Saarland, northern Baden-Wurttemberg, eastern Mecklenburg-Hither Pomerania, and a strip upstream on the Oder as far as the Guben-Cottbus-Forst region.